Triple positive solutions of BVP for second order ODE with one dimensional laplacian on the half line - Liu, Yuji (2014)
By applying Leggett-Williams fixed point theorem in a suitably constructed cone, we obtain the existence of at least three bounded positive solutions for a boundary value problem on the half line. Our result improves and complements some of the work in the literature.